2016
DOI: 10.1111/jvim.14570
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Leptin and Adiponectin in Dogs with Myxomatous Mitral Valve Disease

Abstract: BackgroundThe concentrations of circulating adipokines in dogs with myxomatous mitral valve disease (MMVD) have not been investigated in detail.ObjectivesTo determine whether serum concentrations of adipokines differ between healthy dogs and dogs with MMVD and whether circulating concentrations depend on the severity of heart failure resulting from MMVD.AnimalsIn the preliminary study, 30 healthy dogs and 17 client‐owned dogs with MMVD, and in the subsequent study, 30 healthy dogs and 46 client‐owned dogs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 68 publications
1
23
0
1
Order By: Relevance
“…Tumor necrosis factor-α (TNF), for example, is elevated in both dogs and cats with CHF [38,44]. Two recent studies found increased concentrations of leptin and decreased concentrations of adiponectin in dogs with CHF, but the association between cachexia and adipokines has not been evaluated [45,46]. As in humans with CHF, circulating insulin-like growth factor-1 (IGF-1) concentrations were shown to be an independent predictor of survival in dogs with CHF [38,47].…”
Section: Cardiac Cachexia In Dogs and Catsmentioning
confidence: 99%
“…Tumor necrosis factor-α (TNF), for example, is elevated in both dogs and cats with CHF [38,44]. Two recent studies found increased concentrations of leptin and decreased concentrations of adiponectin in dogs with CHF, but the association between cachexia and adipokines has not been evaluated [45,46]. As in humans with CHF, circulating insulin-like growth factor-1 (IGF-1) concentrations were shown to be an independent predictor of survival in dogs with CHF [38,47].…”
Section: Cardiac Cachexia In Dogs and Catsmentioning
confidence: 99%
“…Adipokines, including leptin, adiponectin and resistin, are biologically active substances that are secreted mainly from mature adipose tissue, playing important roles in the regulation of the lipid and carbohydrate metabolism [11,12]. Because leptin primarily works as a fasting hormone thorough the regulation of food intake and energy consumption, plasma leptin levels are quantitative markers of obesity in humans, dogs and rodents [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that adiponectin contributes to increased insulin sensitivity, reduced blood glucose and reduced tissue TG levels in the liver and muscle [14]. Resistin promotes inflammation and regulates the secretion of proinflammatory cytokines such as TNF-α and interleukin-6 (IL-6) [11][12][13][14][15]. However, there was only a slight change in adiponectin and no change in resistin over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Observed dogs were not suffering from obesity, so found leptin changes are connected with heart failure syndrome. In addition, the correlation between leptin level and heart failure severity was found [45].…”
Section: Regulation Of Carbohydrates and Ffa Oxidationmentioning
confidence: 98%